2015
DOI: 10.1002/pnp.375
|View full text |Cite
|
Sign up to set email alerts
|

Management of depression in children and adolescents

Abstract: As part of our series on managing neurological and psychiatric conditions in children and adolescents, Dr Julia Gledhill and Dr Matthew Hodes discuss depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Antidepressants can be used in the management of Major Depression, Anxiety, Seasonal Affective Disorder (SAD), OCD, PTSD and Social Anxiety. They may also be used to treat enuresis and pre-menstrual syndrome[ 141 ].…”
Section: Psychopharmacology Of Childhood Behavioural and Emotional DImentioning
confidence: 99%
“…Antidepressants can be used in the management of Major Depression, Anxiety, Seasonal Affective Disorder (SAD), OCD, PTSD and Social Anxiety. They may also be used to treat enuresis and pre-menstrual syndrome[ 141 ].…”
Section: Psychopharmacology Of Childhood Behavioural and Emotional DImentioning
confidence: 99%
“…Psychological, social and cognitive factors are found to be involved in creating mental as well as emotional turmoil for children and adolescents and result in causing depressive disorders. Gledhill and Hodes (2015) identified that from the biological or genetic perspective, various elements are involved that may cause depression among children. For example, genetic causes may include brain trauma, development disorders, genetic influence or chemical imbalances.…”
Section: Causes and Implications Of Depression Among School Childrenmentioning
confidence: 99%
“…Compared to adults, symptoms of depression in children may be more characterized by irritability than by low mood. Depression may deteriorate children's functionality in home and school settings [28].…”
Section: The Achenbach System Of Empirically Based Assessmentmentioning
confidence: 99%